2003
DOI: 10.1023/a:1026236726568
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Although no single or combined donor or recipient variable(s) could be identified as predictor(s) of pregnancy, the data suggest that donors < or = 33 years of age with basal cycle day 3 serum levels of FSH 4-8 IU/L, LH < 8 IU/L, and E2 < 70 pg/mL had an optimal outcome. Transfer of two selected embryos on day 3 yields a favorable pregnancy outcome while significantly decreasing the occurrence of multiple pregnancies. These policies, in addition to embryo cryopreservation, were associated with optimal pregnanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…reported CPR, AR, and MPR in OD cycles to be 47%, 19%, and 35%, respectively. [ 16 ] These results are comparable to present study which showed CPR (50.2%), AR (21.8%), and MPR (32.5%). A systematic review by Thomopoulos et al .…”
Section: Discussionsupporting
confidence: 90%
“…reported CPR, AR, and MPR in OD cycles to be 47%, 19%, and 35%, respectively. [ 16 ] These results are comparable to present study which showed CPR (50.2%), AR (21.8%), and MPR (32.5%). A systematic review by Thomopoulos et al .…”
Section: Discussionsupporting
confidence: 90%
“…No significant association was found between endometrial thickness and implantation rate but pregnancy outcome was improved in patients showing an endometrial lining thickness >8 mm. [16] Endometrial pattern in artificially prepared cycles does not influence pregnancy prognosis. [12]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that donor age is a predictive factor of live birth (LB) outcomes (310). Mirkin et al suggested that a baseline follicle stimulating hormone (FSH) between 4 and 8 IU/L was predictive of IVF outcomes (8). In contrast, Barton et al did not observe an association between FSH levels and LB outcomes (11), and observed that the total number of oocytes retrieved was associated with greatest probability of live birth (12).…”
Section: Introductionmentioning
confidence: 99%